Comparative study of sinusoidal pulse-width and hysteresis modulations in current source inverter - Taufik, N. N. (2007)
In this paper, modeling and comparative analysis of Current Source Inverter (CSI) using Sinusoidal Pulse-Width-Modulation (SPWM) and Hysteresis Modulation (HM) will be presented. The modeling of both CSI-SPWM and CSI-HM are implemented using OrCAD Pspice. Results from the simulations will be presented along with the performance analysis of both inverters. More specifically, comparative analysis pertaining to output current regulation, harmonic contents, and transient response will be discussed. Moreover, further investigation about the effect of current THD, power factor and efficiency for balanced and unbalanced three-phase input sources with ±1%, ±3%, ±5% rms variation at the converter stage to various output loads will be described.